Duhovna oskrba žensk po spontani prekinitvi nosečnosti - Macuh, Zala (Obzornik zdravstvene nege, 2024)
Introduction: Termination of pregnancy represents a major distress for the woman, her partner and family, as well as for the medical staff who need to provide comprehensive health care, of which spiritual care is an essential aspect. The aim of the literature review is to identify the type of spiritual care that women need after a spontaneous miscarriage.Methods: A systematic literature review was conducted in April 2023 in the CINAHL Ultimate, Science Direct, Wiley Online Library, and Web of Science databases using an English-language search string. The search, review, and selection of articles followed the PRISMA guidelines. The articles were critically appraised. The data collected were analysed using the method of content analysis.Results: The literature search yielded 490 studies, nine of which were included in the final analysis. The main category consisted of three subcategories: (1) Emotions and Feelings, (2) Interpersonal Relationships, and (3) Spiritual Growth.Discussion and conclusion: The results show that spiritual care requires an understanding of women's spiritual needs and distress after a spontaneous termination of pregnancy. After a miscarriage, women desire quality spiritual care in addition to medical care. Women tend to express their spiritual needs through emotions and feelings, which need to be recognised and responded to appropriately by nurses and midwives. Spiritual care should be based on understanding, compassion and support.
Keywords: duhovne potrebe; duhovnost; miscarriage; spiritual needs; spirituality; spontani splav